Penerapan Rekayasa Nilai (Value Engineering) pada Proyek Pembangunan Gedung Kantor Pusat Layanan Haji dan Umroh Terpadu Kementerian Agama Kab. Batanghari - Adella Sumarda; Annisaa Dwiretnani; Wari Dony (Universitas Batanghari Jambi, 2022)
Value Engineering (VE) or in Indonesian called Value Engineering is a method that analyzes the problems of a project through a systematic and organized approach by eliminating unnecessary costs without reducing the function, appearance, quality and reliability of the project. In accordance with the regulation of the Ministry of Public Works No. 222/KPTS/CK/1991, the Directorate General of Human Settlements stated that buildings with a value of over 1 billion must be carried out a Value Engineering analysis. Value engineering can be viewed in terms of materials or materials, implementation methods and implementation time. The application of the value engineering method in the Construction of the Integrated Hajj and Umrah Service Headquarters of the Ministry of Religion, Batang Hari Regency, is reviewed in terms of architectural work, namely by reviewing the use of materials in Floor, Ceiling, Roofing, Sills work. Value engineering analysis is carried out in five stages, namely: Information Stage, Creative Stage, Analysis Stage, Development Stage, and Percentage/Recommendation Stage. The information stage is carried out to look for work items that have the potential to have high costs, this can be done by means of a cost model, breakdown, and Pareto analysis. Based on the Pareto analysis, there are 5 work items that have the potential to be carried out by value engineering. In the creative stage, alternative ideas are generated where the quality, function and quality are the same, but at a lower price. The development stage is a comparison between the alternatives that will be obtained at the analysis stage. The recommendation stage is the result of the selected alternatives. At the recommendation stage, the results of the application of the value engineering method are that the material used for floor installation work is 60x60 ceramic, for ceiling work is plywood, for roof work is sand metal tile, for door frame work, windows and ventilation are aluminum frames. Alexindo 4 inch. The total cost before applying value engineering is Rp. 1,454,030,488,23 after applying value engineering there is a cost of Rp. 1,408,960,835.40. The cost efficiency that can be applied in this Development Project is 3%. The value engineering method can reduce the cost of planning the construction of the Integrated Hajj and Umrah Service Center Office Building, Ministry of Religion, Batang Hari Regency.